Regulation of NMDA Receptor Plasticity in the BNST Following Adolescent Alcohol Exposure - Carzoli, Kathryn L.; Sharfman, Nathan M.; Lerner, Mollie R.; Miller, Miriam C.; Holmgren, Eleanor B.; Wills, Tiffany A. (Frontiers in Cellular Neuroscience, 2019)
PPersistent alterations in synaptic plasticity and neurotransmission are thought to underlie the heightened risk of adolescent-onset drinkers to develop alcohol use disorders in adulthood. The bed nucleus of the stria terminalis (BNST) is a compelling region to study the consequences of early alcohol, as it is innervated by cortical structures which undergo continued maturation during adolescence and is critically involved in stress and negative affect-associated relapse. In adult mice, chronic ethanol induces long-term changes in GluN2B-containing NMDA receptors (NMDARs) of the BNST. It remains unclear, however, whether the adolescent BNST is susceptible to such persistent alcohol-induced modifications and, if so, whether they are preserved into adulthood. We therefore examined the short- and long-term consequences of adolescent intermittent ethanol exposure (AIE) on NMDAR transmission and plasticity in the BNST of male and female mice. Whole-cell voltage clamp recordings revealed greater glutamatergic tone in the BNST of AIE-treated males and females relative to air-controls. This change, which corresponded to an increase in presynaptic glutamate release, resulted in altered postsynaptic NMDAR metaplasticity and enhanced GluN2B transmission in males but not females. Only AIE-treated males displayed upregulated GluN2B expression (determined by western blot analysis). While these changes did not persist into adulthood under basal conditions, exposing adult males (but not females) to acute restraint stress reinstated AIE-induced alterations in NMDAR metaplasticity and GluN2B function. These data demonstrate that adolescent alcohol exposure specifically modifies NMDARs in the male BNST, that the plastic changes to NMDARs are long-lasting, and that they can be engaged by stress.